1990
DOI: 10.1148/radiology.176.3.2167501
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic breast biopsy with a biopsy gun.

Abstract: One hundred three patients underwent stereotactic breast biopsy with an 18-, 16-, or 14-gauge cutting needle and a biopsy gun. After biopsy, a localization wire was placed and surgical biopsy performed. There was agreement of the histologic results in 89 cases (87%) including 14 of 16 cancers (87%) (kappa = 0.806). The gun biopsy yielded the correct diagnosis in four cases involving a lesion (including one cancer) that was missed at the surgical biopsy. Nine cases in which the lesion was missed at gun biopsy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
126
0
10

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(139 citation statements)
references
References 0 publications
3
126
0
10
Order By: Relevance
“…- 3 Two open-biopsy specimens were incorrectly diagnosed as DCIS (i.e., expert panel reclassified final histologic diagnosis as benign).- 4 Ten lesions diagnosed as DCIS and 3 diagnosed as invasive cancer on large-core needle biopsy contained only benign or normal breast tissue at excision biopsy. Panel review showed that the needle biopsies of 5 of these lesions (1 invasive and 4 DCIS) were incorrectly diagnosed as malignant by the pathologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…- 3 Two open-biopsy specimens were incorrectly diagnosed as DCIS (i.e., expert panel reclassified final histologic diagnosis as benign).- 4 Ten lesions diagnosed as DCIS and 3 diagnosed as invasive cancer on large-core needle biopsy contained only benign or normal breast tissue at excision biopsy. Panel review showed that the needle biopsies of 5 of these lesions (1 invasive and 4 DCIS) were incorrectly diagnosed as malignant by the pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…One of these alternatives is the stereotactic large-core needle biopsy on a prone biopsy table. 3 In the United States, the stereotactic large-core needle biopsy is now generally accepted as an alternative for open-breast biopsy. 4,5 Much has been written about the diagnostic accuracy of this technique, but the number of studies with adequate surgical or clinical follow-up is limited 6 and in several studies patient selection took place.…”
mentioning
confidence: 99%
“…Previous studies have shown that while CNB is highly reliable and sensitive for distinguishing between malignant and benign disease [1][2][3], it is less reliable for diagnosing atypical ductal hyperplasia (ADH). For patients diagnosed with ADH at CNB, the rate of upgrade to ductal carcinoma in situ or invasive cancer at follow-up surgical excision is reported as 19-87% [4][5][6][7][8][9]. Therefore, follow-up surgical excision is generally recommended when ADH is diagnosed at CNB.…”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic coreneedle breast biopsy described by Parker et al [1] is widely used for the evaluation of non-palpable breast lesions. In addition to high sensitivity and specificity in confirming malignant tissue in suspicious breast lesions [2], core samples also allow preoperative determination of histological prognostic factors such as grade, type, and invasion of neoplasm, as well as ER, PR and HER-2 status by immunohistochemistry (IHC) [3Á5].…”
mentioning
confidence: 99%